(untitled) (JONAH : Journal of Nursing and Homecare, 2025)
Preschool children are children aged 3-6 years, during this period children’s development is very rapid. One very important development is the development of fine motor skills, because it will make it easier for children to carry out their activities. Fine motor skills develop optimally by being stimulated, namely Puzzle Play Therapy can be applied. Research Objective: To describe the application of puzzle play therapy to fine motor development at the Nurul Azhar Preschool & Kindergarten. Research Method: This research is descriptive using a case study approach with 2 subjects, conducted on April 22–May 3 2024. In this research, data was collected by observation and presented in narrative form. Research Results: showed that the fine motor development of both subjects before being given the intervention had failed and after the intervention for 2 weeks with 6 meetings, both subjects found that their fine motor development had increased towards pass. Conclusion: The results of the study showed an increase in the fine motor development of preschool children after the puzzle playing therapy intervention.